Implementasi Sistem E-Commerce Berbasis Web Menggunakan Laravel pada PT. Saveta - Muhammad Afif Hidayat; Idham Fatirrohman Syufi (YASIN, 2026)
The development of information technology encourages companies to carry out digital transformation in various business activities, including sales processes and transaction management. However, PT Sarana Veterinaria Jaya Abadi still carries out part of its sales process semi-manually through communication media and conventional record keeping, which may lead to data errors, stock discrepancies, and delays in presenting information for the company and customers. This study aims to design and implement a web-based E-Commerce system using the Laravel framework as a solution to improve sales management efficiency, accelerate transaction processes, and support the provision of more accurate and integrated information. This study used the Waterfall method, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. Research data were obtained through observation, interviews, and literature study to ensure that the developed system aligned with the company’s operational needs. The results show that the developed E-Commerce system is able to integrate product management, shopping cart, checkout, payment, order monitoring, and sales report preparation processes into a single platform. Based on Black Box Testing, all main system functions ran properly and in accordance with user needs. The conclusion of the study affirms that the implementation of a Laravel-based E-Commerce system can improve the effectiveness and efficiency of the sales process through faster, more accurate, and integrated data management. The implications of this study provide practical contributions for the company in supporting the digitalization of business processes, improving customer service quality, and providing transaction information that can be monitored in real time to support more appropriate decision-making.